Diaconia under mission drift: problems with its theological legitimation and its welfare state partnership - Eurich, Johannes (Diaconia, 2012)
Reiner Anselm (Diaconia 2/2011) claims that the German diaconia has to concentrate more on its Biblical roots like compassion, etc. For Anselm the German diaconia has become part of a social welfare system with few or no connections to the specificity of what diaconia means. The article opposes Anselm. Biblical diaconia cannot only stick to the pious part of the tradition. The Old Testament favours social justice for all the poor. Social justice is not something external to diaconia. This is also supported by theology and modern ethics.